Social context as a pillar of sustainable forest management - a Slovenian case - Bogataj, Nevenka (Zbornik gozdarstva in lesarstva, 2009)
Social context as more or less neglected field of sustainable development is crucial for the implementation of forest management measures. We can consider it as a basis to cope with (changing) social structure characteristics. Rationalisation of public services, which we face when coping with economic crisis, might take this into consideration. The Forest Service network serves as a scanner of needs in their social context. It is also a respondent to local specifics in the form of forest management measures. Evidence of research on the social research in Slovenian forestry is weak, although not non-existent. We tested a system approach, a structuring method of general public. Segmentation, a method presented, is generally known in marketing and has not been used in Slovenian forestry up to now. The two-step clustering analysis of quantitative and qualitative data gathered with an inquiry of study circles (form of community learning) was used and is described herewith.The results show three general value based segments of study circle participants. The role of Slovenian forestry is changing and is not independent of its dynamic and colourful social contexts. Recognition of the society structure and dynamics may contribute to the rationalisation of organisational models during the crisis period. However, grounded actualisation of recent organisational models is possible only by considering priorities of the society s segments. We conclude with a suggestion for more R&D engagement in the social pillar of multifunctional forest management, in particular as the Slovenian social context is defined by dominance of private property and forest owners ageing, which are far from being analysed and responded to.
Keywords: družbena struktura; forestry; gozdarstvo; pretok informacij; pretok znanja; segmentacija; Slovenia; Slovenija; sustainable development; trajnostni razvoj